IDENTIFICATION OF POTENTIAL BACTERIAL PATHOGENS IN THE MICROBIOME OF WILD CYPRINID (CYPRINIDAE) FISH FROM THE ISHIM (ESIL) RIVER USING HIGH-THROUGHPUT SEQUENCING - S. Suleymenova; M. Kumar; S. Nuralibekov; T. Sabyrzhan; Ye. Kassymbekov; M. Yessentureyeva; Y. Shayakhmet; K. Isbekov; S. Assylbekova; O. Kirichenko; Z. Bolatbekova; A. Kydyrmanov (Animal Health and Biosafety, 2026)
The bacterial microbiome of wild freshwater fish in Kazakhstan is still poorly characterized, and data on the taxonomic composition of bacterial communities in their natural populations are limited. In this regard, the study investigated bacterial communities of pooled samples prepared from tissues of wild fish belonging to the Cyprinidae family caught from the Ishil River using the shotgun metagenomic sequencing method. Two independently prepared libraries were sequenced on the Illumina MiSeq and NovaSeq platforms, which allowed for comparison of bacterial profiles obtained from different sequencing data. Clear differences were observed between the bacterial composition of the two samples. While representatives of the Moraxellaceae family dominated in the MiSeq data, the relative proportion of the Aeromonadaceae and Fusobacteriaceae families was higher in the NovaSeq data. At the genus level, Psychrobacter and Moraxella were dominant in the MiSeq library, while the genera Aeromonas, Fusobacterium, and Cetobacterium were more abundant in the NovaSeq library. Species-level analysis also revealed thatpecies-level analysis likewise showed that Aeromonas media, A. hydrophila, and A. caviae were among the most frequently identified taxa in the NovaSeq dataset. Compared with the NovaSeq sample, the MiSeq sample showed a more diverse composition of the bacterial community. In addition, several bacterial taxa associated with fish diseases or opportunistic infections were identified, including A. hydrophila, Edwardsiella anguillarum, Plesiomonas shigelloides, and Vibrio spp. The observed differences between the two pooled samples may be due to biological variability between fish groups, as well as differences in sequencing depth. Overall, this study adds to the knowledge about bacterial communities associated with wild freshwater Cyprinidae fish in Ishil River and demonstrates that shotgun metagenomic sequencing can be an effective tool for future monitoring of fish health and freshwater ecosystems.